Supplementation of organic acids on weight gain, mortality and intestinal integrity of broiler chickens - Chopin-Rodríguez, José Miguel (2024)
In animal production, controlling the growth of pathogenic or opportunistic microorganisms is essential to ensure both human and animal health, as well as to improve productive performance. In this context, the present study aimed to evaluate the effect of organic acids supplemented in drinking water on the productive parameters of broiler chickens. The experiment was conducted at the experimental field of the Salvadoran University Alberto Masferrer, located in Zapotitan, El Salvador, using two groups of 200 Cobb MX broiler chickens each. One group, referred to as the "Treatment" group, received a registered commercial product in their drinking water containing a mixture of four organic acids: citric acid (1.0%), ascorbic acid (1.1%), lactic acid (0.9%), and acetic acid (0.9%). The second group, designated as the "Control" group, did not receive this acid mixture. Various productive parameters were evaluated, such as weight gain, mortality, and intestinal integrity. Additionally, cloacal swabs were collected to analyze differences in intestinal microbiota. Results showed the absence of two bacterial genera, Clostridium perfringens, and Bordetella sp., in the Treatment group compared to the Control group. The treated group demonstrated significantly superior productivity outcomes, with a 10.72% increase in weight (p < 0.05) and a reduction in mortality to 1.50%, compared to 3.00% in the untreated group. Furthermore, improved intestinal integrity was observed in animals that received the acid mixture. These findings highlight the potential of the evaluated products, suggesting the need for further research into their effects to optimize poultry production.